Study on the operational characteristics of central area transit (CAT) Georgetown, Penang - Lok, Kok Sheng (2018)
The increasing flow of tourists into Georgetown along with the declaration of World Heritage Site by UNESCO has leaded to the introduction of free shuttle bus which is Rapid Penang Central Area Transit (CAT) Georgetown. This is an alternative mode of transport provided for the convenience of tourist and local community besides helps in pollution and traffic congestion control. This research was aimed to study the demography of CAT Georgetown user and the service performance from the perception of user. Besides, origin destination map will be constructed to understand the travel pattern of the user using the CAT Georgetown service. The research was carried out within the service area of CAT Georgetown which consists of 19 stations in the UNESCO World Heritage Site. The research was conducted using questionnaire survey method and on board study to collect the required data. A total of 70 questionnaires were distributed randomly to the respondent without preference. The collected completed questionnaires were then analyzed using Microsoft Excel for the Descriptive Analysis on the demography. The performance of CAT Georgetown was analyzed using the Statistical Package for the Social Sciences (SPSS) software which including Pilot Test, Reliability Test and Normality Test. Besides, a total of 4 origin destination maps (ODM) were drawn. The maps were consisted of 2 from stations to Komtar Bus Terminal station and 2 from stations to Ferry station both on weekday and weekend respectively. An origin destination map matrix was drawn to show the full picture of travel habit of respondent. These 2 stations were the most saturated service station of CAT Georgetown. Finally, suggestions and recommendations were given based on the results of the research to improve the CAT Georgetown service in the future. The findings of the research help both the local authorities and CAT Georgetown authorities in doing future planning of CAT Georgetown to provide a better service and make it as the first choice of the transportation among the user in the future.